Pathological and Biochemical Studies on "Fatty Liver and Kidney Syndrome" in White Broiler Chickens Fed with Ration Including Rendering Oil - Karadaş, Erkan; Özer, Harun; Beytut, Enver; Özdemir, Necmi (My University, 1999)
The "Fatty Liver and Kidney Syndrome" (FLKS) was induced experimentally in white broiler chickens. Eighty chickens of ten-day-old were divided into equally five groups. These chickens were fed with a daily provided commercial ration containing poultry rendering oil in a ratio of 0% in group I (control group), 5% in group II, 10% in group III, 15% in group IV and 20% in group V for eight weeks. Total mortality was 18.75%. Although group II chickens did not show significant clinical, morphological and biochemical findings, these findings were found to be significant in groups III, IV and V. In these three groups, an increase in total body weight; the colour changes in the feathers ranging from dark-yellowish to brownish degree; paleness and enlargement of combs and wattles were determined to be the most important clinical findings. At necropsy, affected birds had an abnormal deposits of fat in subcutaneous tissues, abdominal cavity, and visceral organs and tissues. Although weights and sizes of the liver, kidney and heart increased, the weight of the thymus decreased. In addition, enlargement in volume, fragility in consistency and roundness in the edges of lobes and a light yellow or yellowish-brown colour in appearence of the liver; a left ventricular dilatation and solidity on the wall of the left ventricle; atherosclerosis in the thoracic aorta, and testicular hypoplasia were found to be other marked macroscopical lesions. Microscopically, a diffuse fatty degeneration in both epithelial cells of the liver and proximal convoluted tubules of the kidney, and also generalised diffuse glomerular lipidosis in the latter organ were the most noticeable findings reflecting the macroscopic lesions. Results of biochemical tests in the serum, plasma and tissue homogenates revealed the presence of pronounced increases in levels of triglycerides, free fatty acids, total lipid, pyruvate and isositric dehydrogenase enzyme (P<0.001) and a decrease in level of aspartate aminotransferase enzyme (P<0.001) associated with hypoglycaemia (P<0.001).
Rendering Ya?i İçeren Yemle Beslenen Broiler Piliçlerde "Karaci?er-Böbrek Ya?lanmasi Sendromu" Üzerinde Patolojik ve Biyokimyasal Araştirmalar
Keywords: Chickens; Fatty Liver and Kidney Syndrome; Morphology; Rendering Oil